WAYS TO INCREASE THE EFFICIENCY OF GINING MACHINE - Muradov, Rustam (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
In the process of separating cotton fiber from seeds, special attention is paid to preserving the original quality indicators of the fiber and seeds, creating technologies and equipment to control the quality of the product. The economic position of cotton ginners depends on the quality of the fiber produced by the cotton gin. Therefore, research will need to be done to obtain quality fiber in the gin machine.